Somatic depression: medical and psychological support - Hapon Анастасія (Psychosomatic Medicine and General Practice, 2023)
Various disorders of the affective sphere of the psyche are one of the most frequently diagnosed forms of mental pathology. As medical practice shows, hidden depression occupies a significant share among somatized mental disorders. Despite the large number and volume of research, the problem of somatized depression is one of the most difficult in modern psychiatry and medical psychology. Often, primary care physicians do not detect mental disorders in their patients. According to research results, doctors "miss" patients’ mental health problems 20-80% of the time. Most patients do not attach due importance to the symptoms they have, devalue them, do not realize the need for proper specialized diagnosis, or engage in self-medication. This is what precedes serious consequences, such as difficulty in diagnosis, differential diagnosis, and the appointment of inappropriate treatment in the form of symptomatic therapy instead of pathogenetic therapy. Currently, depressive disorders are diagnosed in people of working and creative age (20-40 years old), which strengthens the socio-economic significance of the problem of depression detection. The problem of somatized depression is that patients do not complain about any symptoms of depression, but also somatic complaints, which can be manifested, for example, by chronic pain in various organs and systems, disorders of the gastrointestinal tract and cardiovascular system, or sleep disturbance, remain despite the presence of drug treatment in the form of analgesics, barbiturates, cardiac glycosides, etc. The purpose of the work: to investigate the features and essence of masked depression, its influence on the development of somatic symptoms, exhaustion depression, its prevention, and methods of combating it. Research methods: clinical material for the study was 35 respondents aged 18 to 50 years. In addition to the socio-demographic study, the following were used: the Beck Depression Scale, which makes it possible to determine the presence of depression in a person and the degree of its severity, and the Hamilton Anxiety Rating Scale (HARS). Examination results. During the work, according to the results of the survey, it was established that 16 people have no depressive symptoms, 10 people have a mild degree of depression (sub-depression), which corresponds to 10-15 points, 3 people have a moderate level of depression, which is expressed in 16-19 points, 6 interviewees have depression of moderate severity (pronounced depression corresponding to 20-29 points) and no persons with a severe level of depression were found.